Calnexin, an ER-induced protein, is a prognostic marker and potential therapeutic target in colorectal cancer. Issue 1 (December 2016) - Ryan, Deborah; Carberry, Steven; Murphy, Áine; Lindner, Andreas; Fay, Joanna; Hector, Suzanne; McCawley, Niamh; Bacon, Orna; Concannon, Caoimhin; Kay, Elaine; McNamara, Deborah; Prehn, Jochen
Abstract Background Colorectal cancer (CRC) is a leading cause of cancer mortality in the Western world and commonly treated with genotoxic chemotherapy. Stress in the endoplasmic reticulum (ER) was implicated to contribute to chemotherapeutic resistance. Hence, ER stress related protein may be of prognostic or therapeutic significance. Methods The expression levels of ER stress proteins calnexin, calreticulin, GRP78 and GRP94 were determined in n = 23 Stage II and III colon cancer fresh frozen tumour and matched normal tissue samples. Data were validated in a cohort of n = 11 rectal cancer patients treated with radiochemotherapy in the neoadjuvant setting. Thecalnexin gene was silenced using siRNA in HCT116 cells. Results There were no increased levels of ER stress proteins in tumour compared to matched normal tissue samples in Stage II or III CRC. However, increased calnexin protein levels were predictive of poor clinical outcome in the patient cohort. Data were validated in the rectal cancer cohort treated in the neoadjuvant setting.Calnexin gene-silencing significantly reduced cell survival and increased cancer cell susceptibility to 5FU chemotherapy. Conclusion Increased tumour protein levels of calnexin may be of prognostic significance in CRC, and calnexin may represent a potential target for future therapies.